Jewish folksong: an ethnomusicological study of categories of Yiddish folksongs within the context of Jewish life in Eastern Europe, from the nineteenth century up to World War II, including partisan songs, and songs of the Holocaust and resistance - Singer, Sara Fay (College of Music, 2025)
This study sets out to provide a cultural analysis of 56 Yiddish folksongs which are representative of some of the bestknown folksong styles among Ashkenazi Jews. Actual research was carried out over two years, mainly in Cape Town, with short visits abroad to the United Kingdom, and to Israel. The research procedure is based on Gerhard Kubik's 'integrated-study' approach. Accordingly, I approached my subject from several perspectives: historical, sociological, musicological, literary, and linguistic - and researched it on an emic basis. The research material was obtained from a number of sources - from oral information, literature, song collections and sound recordings, and from personal observation. The aim of this study is: (i) to identify intrinsic structural and stylistic features within Yiddish folksongs; (ii) to investigate significant traits concerning their performance practice in their original social contexts, and in presently 'controlled' contexts. The study design is as follows: there are two main parts, Part I and Part II. Part I comprises three chapters: ( i) Chapter 1 is an Introduction giving a historical and socio-cultural overview of Ashkenazi folksong, and the work of pioneer folksong investigators; Chapter 2 surveys historical and political factors which have been largely responsible for the great diversity of Jewish musical traditions, and delineates the various Jewish communities living in geographically defined areas today. The need for comparative studies spanning these different communities is stressed; Chapter 3 is concerned with the history of the Yiddish language, its emergence and development as a spoken language (with dialects), and as a literary language with a standardized orthography; (ii) Part II comprises two chapters: Chapter 1 explains the reasons for my adoption of certain research. procedures, and pays particular attention to the socio-cultural background and content of the songs, and their arrangement according to genre. Each song is handled as a distinct item, and transcriptions and texts of all the songs appear at, or near the end of, each genre description. Recorded performances of 27 of the 56 songs appear on a cassette tape which accompanies this study; their texts and music appear on yellow pages, to make for easy location. Chapter 2 concentrates on the purely musicological aspects of the songs. Particular attention is drawn to the way in which songs of 1 shtetl' (village/ small town) origin have been transformed to accommodate the necessities of their mass distribution. A Summary concludes this study, in which attention is also drawn to the 1 recreative 1 aspects of Yiddish folksongs, which persist despite the impact of the huge Jewish folklore industry, and the mass media. A plea is made for a synchronic 'context sensitive' approach to the study of CURRENT performances of Yiddish music, in different performance environments, along the lines advanced by ethnomusicologist Regula Burckhardt Qureshi (1987). This study contains a Preface, and a Glossary of Yiddish and Hebrew terminology, a Bibliography and a Discography